Penanaman kesadaran pada anak usia dini akan pentingnya hidup sehat - de Fretes, Michael Genesis Bimasatrya; Widjanarko, Kevin; Malonda, David Bryant; Linawati, Nanik (Nur Science Institute, 2024)
This community service aims to raise awareness of the importance of healthy living in early childhood. The event was held at Anak Ceria Kindertanden, Surabaya. The activity lasted three days and was followed by twelve kindergarten students aged five to six. In this activity, learning is delivered through a variety of exciting activities. One of them is a puppet stage that tells about healthy food, which attracts children's attention and makes it easier for them to understand the concept. In addition, healthy food picture coloring activities are also done, giving children the opportunity to express their creativity while learning. A domino card game with a healthy food theme becomes the last activity. At this activity, children can learn while playing. The results of these activities show that students better understand the importance of a healthy lifestyle. It shows that this interactive and enjoyable learning method effectively raises health awareness from an early age.